Crashworthiness performance of kenaf/glass fibre-reinforced epoxy hybrid composite filament winding tube - Abu Bakar, Mohd Supian (2020)
The composite material in energy absorption tube application have gained a tremendous function as sacrificial structure device in automotive, motorsport, train and aerospace applications. Due to various capabilities of composite material in reinforcement structure applications, many researchers have explored to tailor the composite material structure with various parameters to withstand and increases the strength and crashworthiness capability under static and impact load conditions. Composite structure from synthetic material such as carbon fibre-reinforce polymer (CFRP), glass fibre-reinforce polymer (GFRP) and Kevlar has used in many high-performance application as a reinforcement due to light-weight and strong properties, besides, these synthetic materials was not easily degrading and it cause many issues related to waste and environmental, moreover, the operation cost to produce was high. Therefore, this present study was upholding the natural and synthetic fibres as a constituent material in a high-performance hybrid application such as energy absorption tube to reduce the synthetic materials waste. Furthermore, this present study of filamentwound natural/synthetic hybrid composite tube has presented the automated filament winding technique to merging efficiently two distinct fibres into single fibre-band with various parameters related. Besides, this present study has shown the abilities of natural/synthetic hybrid composite tube to withstand the compression load and impact load efficiently compare to single synthetic material. The two aspect parameters in filament-wound kenaf/glass hybrid composite tube in quasi-static compression load and intermediate-velocity impact load experiments have exposed the first parameters of winding orientation in the hybrid composite tube has identified that the high winding orientation was contributed high energy absorption characteristics and stable collapse behaviour performance. Meanwhile, the second parameter of intraply stacking sequence parameter in hybrid composite tube significantly increase 28% of initial peak load and 68% of the energy absorbed compared to the glass fibre-reinforced epoxy tube during compression and impact load experiments. Therefore, from the experimental results, obviously showed that natural fibre as a constituent in hybrid synthetic components has plentiful of potential as a hybrid reinforcement material in structural application device.